Accounting, text and cases - Anthony, Robert Newton, 1916-; Reece, James S.; Hertenstein, Julie Huffman (Chicago : Irwin, 1995)
brief contents two parts financial accounting management accounting .
Includes bibliographical references and index.
All Ages.
Keywords: Accounting; Accounting -- Case studies